Jumping Jenny : a Roger sheringham case - Berkeley, Anthony 1893-1971 (Roger Sheringham Cases, 2001)
When a murder is committed at a party given in honour of a famous writer-detective, the guests impersona te famous murderers and the victim is found hanging from a f ake gallows erected as a joke. '